(untitled) (Journal of Informatics Education and Research, 2026)
The rapid advancement of digital technologies has reshaped economic structures, governance systems, and social well-being globally. This study examines the interconnections between digital infrastructure, digital welfare, quality of life, and sustainable economic growth, emphasizing the mediating role of human capital and institutional quality. Drawing on empirical evidence and comparative analysis between European and Arab countries, the research highlights the conditions under which digitalization contributes positively to socio- economic development. Utilizing a comprehensive conceptual framework, the study integrates multidimensional perspectives of digital welfare, encompassing access, autonomy, participation, and subjective well-being. Findings indicate that robust digital infrastructure significantly enhances digital welfare outcomes, which in turn positively influence both quality of life and sustainable growth. Moreover, the effectiveness of digital transformation is contingent upon digital skills and literacy, which mediate the translation of technological investments into measurable welfare gains. Institutional coherence further ensures that digital initiatives align with societal goals, amplifying economic and social benefits. Cross-regional comparison reveals that European countries outperform Arab counterparts in leveraging digital welfare for inclusive development, primarily due to differences in infrastructure maturity, policy integration, and human capital. These insights underscore the necessity of integrated strategies combining technological investments, skills development, and governance reforms to maximize the socio-economic returns of digitalization. The study contributes to the literature by positioning digital welfare as a central mechanism linking technology, well-being, and growth, offering practical guidance for policymakers seeking sustainable and inclusive digital development.